Social Contexts and Educational Innovation Trends: A Bibliographical Mapping Analysis - Ramírez, Leticia Nayeli Ramírez (2019)
Educational innovation is a pending item on the agendas of international educational institutions. Whereas current educational policies highlight the importance of educational innovation as a key element for improving the quality of education and promoting social development, the social aspect of innovation involves multidisciplinary interaction from a sociocultural perspective. After conducting a systematic bibliographical search of two main databases: SCOPUS and WoS (period ranging from 2013-2017), a total sample (N = 43) was filtered with established inclusion / exclusion criteria (keywords, document type, year of publication, area of discipline) and validity (quality and relevance). The countries with the highest number of publications in this subject are the United States (5), Spain (4) and the United Kingdom (3). The social contexts in which educational innovation strategies have been executed include educational organizations (37), the corporate sector (5) and healthcare institutions (1). Innovation is addressed as it pertains to new ways of organizing activities (29). Findings involve three key social contexts for implementing innovative strategies in six emerging areas of research.